Analisis Flavonoid Total Akar Tabar Kedayan (Aristolochia foveolata Merr) - Siti Jubaidah Jubaidah; Henny Nurhasnawati (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2018)
The tabar kedayan (Aristolochia foveolata Merr) plant located in the Malinau district of East Kalimantan has considerable biological active prospects as antioxidant, antibacterial, antiamuba, anti-inflammatory, antihepatotoxic and antiviral. One of the secondary metabolites in this plant is the flavonoids that can be used as antioxidants.The aim of this research are to analyze total flavonoid content of root tabar kedayan in fractionation with various nonpolar, semipolar and polar solvents. The analysis used in the determination of total flavonoid content using spectrophotometric method. Data of analysis used standard curve method based on absorbance data and concentration of standard solution. The results of this study obtained the highest total flavonoid average on ethyl acetate fraction of 1,09%±0,03 then n-hexane fraction of 0,52%±0,05 and the smallest level of ethanol-water fraction of 0,40%±0,03.